2020
DOI: 10.1093/ptj/pzaa168
|View full text |Cite
|
Sign up to set email alerts
|

“I Have Everything to Win and Nothing to Lose”: Patient Experiences of Mobilization Out of Bed Immediately After Abdominal Surgery

Abstract: Objective Early mobilization is advocated for patients going through abdominal surgery; however, little is known about the patient experience of being mobilized immediately after surgery. The purpose of this study was to explore patient experiences of mobilization immediately after elective abdominal cancer surgery. Methods This interview study used qualitative content analysis. With the use of purposeful sampling, a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Patients generally felt reassured and safe about the healthcare professionals responding promptly when they felt unwell. 30 However, heavy workloads kept healthcare professionals too busy, resulting in a lack of timeliness or continuity in some medical work and patients had to wait for assistance. 36 57 63 64 If there was a delay in diagnosis or help, patients felt frustrated and angry and feared that their prognosis had worsened as a result 48 57 : ‘To begin with, I lost my breath and thought – this can’t be true… You have to ring and ring.’ In addition, patients complained that some questions were left unanswered in time, and they felt uncomfortable to switch to an unfamiliar healthcare professional for help 45 53 : ‘…I thought I would speak to the same doctor who was at the operation, but of course I never saw him again…’…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients generally felt reassured and safe about the healthcare professionals responding promptly when they felt unwell. 30 However, heavy workloads kept healthcare professionals too busy, resulting in a lack of timeliness or continuity in some medical work and patients had to wait for assistance. 36 57 63 64 If there was a delay in diagnosis or help, patients felt frustrated and angry and feared that their prognosis had worsened as a result 48 57 : ‘To begin with, I lost my breath and thought – this can’t be true… You have to ring and ring.’ In addition, patients complained that some questions were left unanswered in time, and they felt uncomfortable to switch to an unfamiliar healthcare professional for help 45 53 : ‘…I thought I would speak to the same doctor who was at the operation, but of course I never saw him again…’…”
Section: Resultsmentioning
confidence: 99%
“…Due to the patients’ vulnerability and sensitivity, they were extremely dependent on the assistance of healthcare professionals during treatment and recovery. 30 In this systematic review, patients mentioned that sometimes they had to wait a long time for help, feedback or responses from their healthcare professionals. After semistructured interviews with multidisciplinary team members, Pearsall et al found that insufficient human resources and unreasonable human resource structure were cited by most as barriers to the implementation of ERAS, 74 indicating that human resource management plays an important role in the implementation of ERAS programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients report that they wake up, feel more alert, regain their autonomy, recover appetite and thirst, and feel that it is easier to breathe when they sit up in a chair compared with when they lie in bed. 44 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that factors such as motivation and physical tiredness influence immediate mobilization in the PACU [ 5 ]. With our approach of repeated mobilization attempts and open communication and support between patient and physiotherapist, we found that the patients remained positive and engaged to further mobilization to try to reach higher levels of mobility despite barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent ERAS Ò Society guidelines for colorectal surgery [1] recommend that patients should be mobilized out of bed on the day of surgery, at least by sitting in a chair for 2 h, and for the rest of the stay in hospital aim to be out of bed for at least 6 h daily. Performing mobilization at the postoperative anesthesia care unit (PACU) can be perceived as risky, resource-intensive, and with barriers that can be perceived as to high for patients [5,6]. While early mobilization is advocated to prevent postoperative complications [7][8][9], there is lack of evidence how early after surgery the mobilization can be safely initiated and has not been investigated after colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%